Investigation of assisted reproductive technologies (ART) for conservation of Bovidae - Benham, Hayley Marie, author; Barfield, Jennifer, advisor; Graham, James, advisor; Krisher, Rebecca, committee member; Duncan, Colleen, committee member (Colorado State University. Libraries, 2022)
There is an ongoing loss in global biodiversity in both wildlife and domestic species, creating a need to protect and preserve valuable genetics for the maintenance and sustainability of these populations. One of the proposed strategies to combat this loss is through the use of assisted reproductive technologies (ART), not as a replacement to natural breeding but as a strategy to augment and increase the tools we have to preserve genetic diversity. Currently, the application of ARTs is not broadly used as there are gaps in knowledge of species-specific reproductive biology and gamete biology, hindering the ability to make fast progress in implementing these techniques for conservation purposes in species and populations that are rapidly declining. ARTs used in domestic species in the Bovidae family, including cattle, have been developing over the past century, and recently are being adapted for use in non-domestic Bovidae. Arguably, one of the most critical ARTs developed for genetic rescue and conservation goals has been the successful utilization of cryopreservation techniques, which has allowed for the creation of genetic resource banks (GRBs), which are biorepositories for gametes, embryos, and tissues. Through GRBs breeding programs can achieve similar or greater levels of heterozygosity and increase the effective population size as represented by embryos and germplasm, compared to captive populations. In this work, we describe studies developing in vitro oocyte maturation (IVM) and in vitro embryo production (IVP) techniques used for the preservation of valuable bison genetics using gametes collected post-mortem, and cryopreservation techniques of bovine oocytes and ovarian tissue for fertility preservation. Using oocytes collected post-mortem, from bison within the YNP herd (a population with endemic brucellosis) we created disease-free embryos for subsequent transfer into healthy surrogate bison. The transfer of brucellosis-free embryos resulted in the live birth of a healthy brucellosis-negative bison calf. Next, by assessing the follicle size and duration of in vitro maturation (IVM) of bison oocytes collected from abattoir ovaries, out of season, we determined that seasonality does impact oocyte competence and blastocyst production, although viable bison embryos can be created independent of seasonal effects. While cryopreservation of female gametes in bovid species remains experimental, vitrification of oocytes may provide an opportunity for infusing greater genetic diversity into future generations. By assessing mitochondrial function of bovine oocytes during vitrification, we found that germinal vesicle (GV) stage oocytes may require additional support through the vitrification process, as they demonstrated a reduced ability to handle cryo-induced oxidative stress post-vitrification. Additionally, vitrification of bovine ovarian cortical tissue coupled with techniques for vitro activation (IVA) of primordial follicles may be an alternative way to preserve female germplasm. Follicle viability in bovine ovarian cortical tissue was partially preserved after vitrification, making it feasible to biobank vitrified tissue from valuable domestic or wild Bovidae, while in vitro tissue culture and/or IVA treatments significantly reduced tissue and follicle viability was unsuccessful. Further investigation of germline preservation in Bovidae is needed before these techniques can be broadly implemented. These ARTs are a toolbox of approaches to conserve biodiversity and valuable genetics through production, use, and preservation of tissue, gametes and embryos.
Keywords: Bovidae; embryo; oocyte; cryopreservation; assisted reproductive technology; gamete